COMUNICAÇÃO ORGANIZACIONAL EM MEGAEVENTOS ESPORTIVOS: O VOLUNTARIADO NOS JOGOS OLÍMPICOS DO RIO DE JANEIRO, EM 2016 - MESQUITA, FLÁVIO AGNELLI (2020)
This research is part of a study of organizational communication to sport, in this case, to the Olympic Games, in particular, observing an interaction made by the competition organizers with the volunteers, a key stakeholder for the success of the Games. In the case of the competition in Rio de Janeiro, in 2016, there were 50 thousand selected who worked in dozens of different departments, exercising management, organization, information and monitoring roles. From airports to sports arenas, volunteers were there. In this sense, it is vitally important to create effective communication actions for this audience, not only to inform them about the actions, but to motivate them as to the execution of the tasks. Based on Content Analysis, combined with a field survey with a representative sample, it was observed which were the communication materials directed to the volunteers and, together with this, how this public is communicated before, during and after the Games Rio 2016. Despite betting on a remarkably objective, simple and digital communication, being the first Olympic competition to use Facebook as an official platform for interaction with volunteers, some discrepancies in perception are evident when comparing the profiles of volunteers. While the actions differ for young Brazilians, mainly residents of Rio de Janeiro, foreigners and those with a higher economic level revealed deficiencies in the way they were communicated. As it is a mega event, with a stakeholder that is too heterogeneous, a variety of communication tools should be a guiding principle in the communication planning carried out by the Organizing Committee.